The role of science, technology and research in economic development - Ramon L. Clarete; Ernesto M. Pernia; Ammielou Gaduena; Adrian Mendoza (University of the Philippines, School of Economics (UPSE), 2014)
Starting with the premise that technological innovation and economic growth are interactive and mutually reinforcing, this paper argues that in order to have a fighting chance in the Asean Economic Community (AEC), let alone global, competition, the Philippines (PH) needs to appreciably ramp up investment spending in science, engineering, and research and development. To the extent that this is achieved - along with the other ongoing policy and institutional reforms - the economy could in time be on a stronger platform to face up to AEC challenges. The paper first revisits PH's macro-economy, poverty, and economic sectors vis-à-vis its Asean and East Asian neighbors. Next, it examines PH's regional and global competitiveness. Then, it looks into the country's current human resource and intellectual capital investments, mainly in higher education and technical/vocational training, as well as in R&D and innovation. A more focused discussion on the University of the Philippines - the "national university" - vis-à-vis its comparators in AEC, including ways to improve its competitiveness, follows. The final section concludes with some recommendations.
Keywords: F15; J24; O; O3; O31; 330; Science and technology (S&T); Research and development (R & D); Economic development; Higher education institutions (HEIs); Economic integration; Asean; Philippines